2020
DOI: 10.1101/gr.257550.119
|View full text |Cite
|
Sign up to set email alerts
|

Alternative polyadenylation drives oncogenic gene expression in pancreatic ductal adenocarcinoma

Abstract: Alternative polyadenylation (APA) is a gene regulatory process that dictates mRNA 3 ′ -UTR length, resulting in changes in mRNA stability and localization. APA is frequently disrupted in cancer and promotes tumorigenesis through altered expression of oncogenes and tumor suppressors. Pan-cancer analyses have revealed common APA events across the tumor landscape; however, little is known about tumor type-specific alterations that may uncover novel events and vulnerabilities. Here, we integrate RNA-sequencing dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 107 publications
(143 reference statements)
6
64
0
Order By: Relevance
“…Nevertheless, when compared with all DEGs, the genes with shortened 3 UTRs did not tend to be more upregulated in LUAD (p-value = 0.07 and 1, hypergeometric test). This result is consistent with prior analyses in pancreatic ductal adenocarcinoma (Venkat et al, 2020) and other types of cancer (Xiang et al, 2018), suggesting the presence of other mechanisms in regulating gene expression. In addition, we found three genes, COL5A1, COL1A2, and CP with lengthened 3 UTR were upregulated in tumors in both the datasets.…”
Section: Utr Shortening-mediated Loss Of Mirna-binding Sitessupporting
confidence: 92%
“…Nevertheless, when compared with all DEGs, the genes with shortened 3 UTRs did not tend to be more upregulated in LUAD (p-value = 0.07 and 1, hypergeometric test). This result is consistent with prior analyses in pancreatic ductal adenocarcinoma (Venkat et al, 2020) and other types of cancer (Xiang et al, 2018), suggesting the presence of other mechanisms in regulating gene expression. In addition, we found three genes, COL5A1, COL1A2, and CP with lengthened 3 UTR were upregulated in tumors in both the datasets.…”
Section: Utr Shortening-mediated Loss Of Mirna-binding Sitessupporting
confidence: 92%
“…In a large-scale study of AS events in 32 cancer types (including pancreatic adenocarcinoma), the TCGA group found that tumor tissue contains 30% more AS events than normal tissue from the same site 31 . Changes in the use of polyadenylation sites leading to transcripts with different 3′ ends have been observed in PDACs with enrichment for alternative polyadenylation events in genes known to play a role in PDAC development 32 . Analyzing exon-specific microarray data from 28 PDACs and 6 normal pancreas tissues, Wang et al 33 found that exon skipping (14.3%), alternative first exon use (14%), and intron retention (8.4%) represented the three most prevalent categories of differentially spliced events comparing PDAC and normal samples.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that GTEx database collected more than 7,000 normal samples from 449 healthy humans, and gene expression data were treated by the same sequencing platform with TCGA database for minimizing potential batch effects. Previous studies have proved that the gene expression data of TCGA and GTEx can be analyzed and integrated successfully ( Kosti et al, 2016 ; Aran et al, 2017 ; Raphael et al, 2017 ; Zeng et al, 2019 ; Venkat et al, 2020 ). Based on this, we integrated gene expression data from TCGA-PAAD and GTEx including 178 tumor samples and 171 normal samples (4 from TCGA-PAAD and 167 from GTEx).…”
Section: Methodsmentioning
confidence: 99%